Thai Dairy Farmers' Adoption of Automated Disinfectant Production - Akkhasingh, Akkhawit; Vuthisopon, Sujira; Saengnoree, Amnuay; Sonsupap, Somchai (My University, 2026)
Adoption of sustainable on-farm technologies is essential to minimize environmental impacts and improve the sustainability and biosecurity of the livestock industry. Despite growing interest in precision livestock farming, no prior study has examined the psychological and behavioral determinants of dairy farmers' adoption of automated disinfectant production systems, particularly in developing economies. The current research uses structural equation modeling to investigate the determinants of adoption intention for a novel automated on-farm disinfectant production system that requires minimal external chemicals and generates no waste. The data were gathered from 320 members of the Dairy Farming Cooperative of Thailand. The hypothesized model includes the constructs of innovation characteristics, trust in innovation, perceived usefulness and perceived value to explain adoption intention. The model had a good fit (χ²/df = 1.22, RMSEA = 0.02, CFI = 0.99) and accounted for 73% of the variability in adoption intention. Among the variables studied, perceived value showed the strongest direct influence on adoption, followed by perceived usefulness. In addition, innovation characteristics exerted the greatest overall influence on adoption intention through the intermediary factors of trust, perceived usefulness and perceived value. It becomes evident that, to foster sustainable innovation in agriculture, it is essential to convey a value proposition that goes well beyond its functional aspects, with trust an indispensable factor in the process. The outlined model provides theoretical and practical views that can enhance the implementation of innovative livestock management techniques.
Keywords: Adoption Intention; Dairy Farm Management; Innovation Diffusion; Precision Livestock Farming (PLF); Sustainable Agriculture; Thailand